If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 2) + -3x + -6 = 0 Reorder the terms: (2 + x)(x + 2) + -3x + -6 = 0 Reorder the terms: (2 + x)(2 + x) + -3x + -6 = 0 Multiply (2 + x) * (2 + x) (2(2 + x) + x(2 + x)) + -3x + -6 = 0 ((2 * 2 + x * 2) + x(2 + x)) + -3x + -6 = 0 ((4 + 2x) + x(2 + x)) + -3x + -6 = 0 (4 + 2x + (2 * x + x * x)) + -3x + -6 = 0 (4 + 2x + (2x + x2)) + -3x + -6 = 0 Combine like terms: 2x + 2x = 4x (4 + 4x + x2) + -3x + -6 = 0 Reorder the terms: 4 + -6 + 4x + -3x + x2 = 0 Combine like terms: 4 + -6 = -2 -2 + 4x + -3x + x2 = 0 Combine like terms: 4x + -3x = 1x -2 + 1x + x2 = 0 Solving -2 + 1x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-2 + -1x)(1 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-2, 1}
| 4(n-5)=4 | | 26x+21=(-39x)-10 | | x+x+20+(210-3x)=180 | | 4.46x+8.92=17.84 | | 4.46+8.92=17.84 | | 15g+45=5[k-10] | | 15g+45=[k-10] | | (2+4)2= | | 3w-12=3w-12 | | y=10/17-x | | log(4)x+log(4)(x+12)=3 | | x^2+y^2+4x-10y=20 | | 4X-16=16X | | log(3)(2x+1)+log(3)(x+8)=3 | | p(x)=3x-5 | | Log(3)(3x+4)=2 | | Log(3)(3x+4)=-2 | | 4(x+1)(x+1)=2(x+1)(2x-3) | | (m-2)+(m-5)+(m-7)+2+6+5+7=m | | 3xsquare-5x+2=0 | | 2z^2-3=-z-2 | | Log(3)(3x-4)=2 | | 9cosx+6sinx=10 | | 2h=4.5 | | x/6=13/24 | | 3*x^2+4*x=5*(2*x+9) | | 9x*x-4x=2x-1 | | -b(4)+6(4)= | | -b+6y= | | 2x+2-2x-3=62 | | 3Y-2(Y+4)=Y+3 | | 20-15m=12-15m |